Effects of an extracurricular program of physical-sports activities on the physical fitness of high school students (RIAF. International Journal of Physical Activity, 2026)
Introduction: The increase in sedentary lifestyles and the use of electronic devices have deteriorated physical fitness in adolescents. Objective: To analyze the effects of an extra-curricular program of physical-sporting activities on physical fitness and Body Mass Index (BMI) in high school students. Methodology: Quantitative study, causal-explanatory type with a pre-experimental design. 36 students (19 males, 17 females; $M_{age} = 16.33$ years) from the Rosa Zárate Educational Unit, Ecuador, participated. Resistance (Cooper), speed (60m), strength (push-ups), and BMI tests were applied before and after an 8-week intervention based on the Self-Determination Theory. Results: The initial diagnosis showed that more than 80% of the sample had deficient levels of physical fitness. After the application, significant improvements ($p < 0.05$) were observed in all variables, highlighting the increase in aerobic endurance and the reduction in the prevalence of overweight. Conclusions: Structured extracurricular programs are effective tools to improve metabolic and functional health in the school environment.
Keywords: Physical activity; high school; physical fitness; students; extracurricular program; health